2012
DOI: 10.3109/00365521.2011.648954
|View full text |Cite
|
Sign up to set email alerts
|

Early postoperative complications in patients with Crohn's disease given and not given preoperative total parenteral nutrition

Abstract: ObjectiveThe effect of preoperative total parenteral nutrition (TPN) on the rate of early (within 30 days) postoperative complications in patients with moderate to severe Crohn's disease (CD) was examined.Material and methodsA series of 15 consecutive patients with CD (mean CD activity index score, 270) given preoperative TPN for 18–90 days (mean, 46 days) and undergoing bowel resection and primary anastomosis was compared with matching controls (105 patients) consecutively selected from all CD patients operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 40 publications
1
84
0
3
Order By: Relevance
“…Another study addressed CDAI scores, indicating that the group receiving preoperative PN had reductions in CDAI to the point of clinical remission by the date of surgery. 45 CDAI was not calculated for control subjects in this study, and statistical significance was not reported for clinical improvement among the PN subjects. One study also concluded that preoperative PN was associated with a smaller length of small bowel requiring resection, confirming earlier findings.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Another study addressed CDAI scores, indicating that the group receiving preoperative PN had reductions in CDAI to the point of clinical remission by the date of surgery. 45 CDAI was not calculated for control subjects in this study, and statistical significance was not reported for clinical improvement among the PN subjects. One study also concluded that preoperative PN was associated with a smaller length of small bowel requiring resection, confirming earlier findings.…”
Section: Discussionmentioning
confidence: 70%
“…Two of the 4 primary articles did not provide information on PN composition. 42,45 Similar to oral intake, PN composition has the potential to alter clinical outcomes significantly; PN composition is also simple data to collect. Controlling for PN composition may be challenging, as patients will likely have different nutrition needs, but documenting what is provided would give better insight into the study context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this study confirmed the association of hypoalbuminemia with anastomotic leak, no prospective studies have conclusively demonstrated that preoperative protein replenishment reduces the risk of anastomotic leak. Jacobson [11] examined the role of pre-operative nutrition prior to surgery but lacked an appropriately matched control group and committed data about fistulas and abscess in the 2 groups. Other studies, including one by Zerbib et al [12], included many interventions at the same time – making it difficult to correlate the outcome with intervention.…”
Section: Discussionmentioning
confidence: 99%